Influence of Social Determinants of Health on Cardiovascular Risk among Patients with Schizophrenia in Mandalay, Myanmar - Wai, Thet Phoo; Sitthimongkol, Yajai; Tankampuan, Thitipong (Nursing Science Journal of Thailand, 2024)
Purpose: To examine the influence of Social Determinants of Health (SDH) on cardiovascular (CV) risk among patients with schizophrenia. Design: Predictive correlational research. Methods: One hundred and forty-five patients with schizophrenia who were attending the Outpatient Department at Psychiatric Hospital in Mandalay, Myanmar were recruited by convenience sampling. Data were collected using demographic and SDH information, and CV RISK tool. Descriptive statistics and linear regression were used for data analysis. Main findings: The findings revealed that 6.3% of the sample were at risk of cardiovascular disease. Education, income, employment, marital status, family support, antipsychotic drugs, duration of illness, and residence jointly accounted for 18% of the variance explained in CV risk (R2 = .18, F (8, 136) = 3.82, p < .001). Among these factors, residence, duration of illness, and employment were significant predictors of CV risk ( = .31, p < .001; = .22, p = .007; = .16, p = .050, respectively). Conclusion and recommendations: This study showed that SDH including residence, illness, and employment were significant predictors of CV risk among patients with schizophrenia. Psychiatric nurses should conduct screening for CV risk at the time of diagnosis of schizophrenia. Supported employment, and behavioral interventions to promote physical activity should be implemented to prevent cardiovascular diseases particularly in patients who were unemployed, had long duration of illness and living in rural areas.